Strategy for Building Customer Loyalty: The Role of Customer Relationship Marketing and Engagement in Mediating Satisfaction - Willy Jack Sumampouw, Ruland; Kemenaung, Dean Salomo Anthonino; Fahrudin, R.A. (SAN Scientific, 2025)
This study investigates the impact of customer relationship marketing and customer engagement on customer loyalty, with customer satisfaction serving as a mediating variable. The sample consisted of 97 service user companies, represented by company administrators working in the field. Hypothesis testing was carried out to examine both the direct and indirect effects, utilizing the mediation function of customer satisfaction. The findings reveal that customer relationship marketing has a direct, positive, and significant influence on customer satisfaction. Additionally, customer relationship marketing directly and positively affects customer loyalty, and customer engagement also has a direct, positive, and significant effect on customer loyalty. However, the results indicate that customer satisfaction does not have a direct, positive, and significant impact on customer loyalty. Furthermore, customer relationship marketing and customer engagement do not influence customer loyalty through the mediation of customer satisfaction. This study adds originality to the existing literature by concentrating on the port logistics service industry, specifically PT. IPC Terminal Petikemas Jakarta has been relatively underexplored in research about customer relationship marketing and engagement. For managerial implications, PT. IPC Terminal Petikemas Jakarta should focus on continually enhancing its customer relationship marketing strategies and actively fostering customer engagement to improve customer loyalty.